A Preliminary Study on the Effects of Lemon Juice and Vitamin C on Postprandial Glucose in Overweight Nondiabetic Adults - Malak Eljafari; Almhgob, Mohamed (AlQalam Journal of Medical and Applied Sciences, 2026)
Postprandial hyperglycemia, together with obesity and elevated body mass index, represents a significant risk factor for the development of type 2 diabetes mellitus. Acidic foods and antioxidants have been suggested to modulate postprandial glycemic responses. This preliminary study aimed to investigate the effects of lemon juice and vitamin C supplementation on postprandial blood glucose concentrations in overweight adults. A randomized crossover trial was conducted in which participants co-ingested a standardized bread meal with water, lemon juice, or vitamin C at two doses (500 mg and 1000 mg). Capillary blood glucose concentrations were measured over a 180-min postprandial period. Co-ingestion of lemon juice and both doses of vitamin C significantly attenuated postprandial glycemic responses compared with water. Peak glucose concentrations were markedly lower following lemon juice and vitamin C supplementation, accompanied by a more gradual post-peak decline. These effects were further reflected by significant reductions in the incremental area under the curve (iAUC₀–₁₈₀) following lemon juice and the higher vitamin C dose, with a borderline reduction observed at the lower dose, indicating a dose-dependent effect. Overall, these findings support a potential role for lemon juice and vitamin C in postprandial glycemic modulation and highlight the need for confirmation in larger, longer-term studies assessing dose–response relationships and their potential to delay progression to type 2 diabetes mellitus.